1987
DOI: 10.1073/pnas.84.22.7972
|View full text |Cite
|
Sign up to set email alerts
|

The regulated expression of erythropoietin by two human hepatoma cell lines.

Abstract: The development of a cell culture system that produces erythropoietin (Epo) in a regulated manner has been the focus of much effort. We have screened multiple renal and hepatic cell lines (including MDCK, LLC-PKI, BHK, WRL 68, CLCL, A704, CRFK, A498, ACHN, TCMK-1, LLC-MK2, CaKi-2, HepG2, and Hep3B) for either constitutive or regulated expression of Epo. Only the human hepatoma cell lines, Hep3B and HepG2, made significant amounts of Epo as measured both by radioimmunoassay and in vitro bioassay (as much as 330… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
174
2
1

Year Published

1991
1991
2003
2003

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 345 publications
(186 citation statements)
references
References 43 publications
9
174
2
1
Order By: Relevance
“…Metabolic enzymes, like aldolase (ALD)-A and -C (Semenza et al, 1994), carbonic anhydrase (CA)-9 (Wykoff et al, 2000), enolase (Eno)-1 , glucose transporter (Glut)-1 and -3 (Sivitz et al, 1992), lactate dehydrogenase (LDH)-A , phosphofructokinase (PFK)-L and -C, phosphoglycerate kinase (PGK)-1 (Firth et al, 1994), and pyruvate kinase (PK)-M (Semenza et al, 1994); 3. Cytokines, growth factors, and other proteins that regulate angiogenesis, vascular permeability, and inflammation, including Epo (Goldberg et al, 1987;Madan and Curtin, 1993), endothelin-1 (Kourembanas et al, 1991), inducible nitric oxide synthase (iNOS; Melillo et al, 1995), plateletderived growth factor-B (Kourembanas et al, 1990), vascular endothelial growth factor (VEGF; Shweiki et al, 1992), and its receptors (VEGFR-1 and -2; Veikkola et al, 2000); 4. Stress proteins, such as the heat shock proteins (HSPs) and cellular redox regulators (Benjamin et al, 1990).…”
Section: Hypoxia-targeted Gene Therapy Cellular Response To Hypoxiamentioning
confidence: 99%
“…Metabolic enzymes, like aldolase (ALD)-A and -C (Semenza et al, 1994), carbonic anhydrase (CA)-9 (Wykoff et al, 2000), enolase (Eno)-1 , glucose transporter (Glut)-1 and -3 (Sivitz et al, 1992), lactate dehydrogenase (LDH)-A , phosphofructokinase (PFK)-L and -C, phosphoglycerate kinase (PGK)-1 (Firth et al, 1994), and pyruvate kinase (PK)-M (Semenza et al, 1994); 3. Cytokines, growth factors, and other proteins that regulate angiogenesis, vascular permeability, and inflammation, including Epo (Goldberg et al, 1987;Madan and Curtin, 1993), endothelin-1 (Kourembanas et al, 1991), inducible nitric oxide synthase (iNOS; Melillo et al, 1995), plateletderived growth factor-B (Kourembanas et al, 1990), vascular endothelial growth factor (VEGF; Shweiki et al, 1992), and its receptors (VEGFR-1 and -2; Veikkola et al, 2000); 4. Stress proteins, such as the heat shock proteins (HSPs) and cellular redox regulators (Benjamin et al, 1990).…”
Section: Hypoxia-targeted Gene Therapy Cellular Response To Hypoxiamentioning
confidence: 99%
“…However, since it has so far not been possible to isolate the cells physiologically producing EPO in liver and kidneys, these studies have been confined to EPO-producing turnout cell lines, and the results obtained with these cell lines are inconclusive and have led to controversial interpretations. Thus, using the human hepatoma cell lines Hep G2 and Hep 3B, which produce EPO in an oxygen-dependent fashion [22] and a renal carcinoma cell line, which secretes EPO constitutively [24], several investigators reported that phorbol esters reduce EPO formation [19,25,31,33]. However, in addition, inhibitors of PKC were found to diminish EPO secretion by Hep G2 ceils [31,33].…”
Section: Introductionmentioning
confidence: 99%
“…8). The two human hepatoma cell lines HepG2 and Hep3B are so far the only permanent cell culture models available to investigate oxygen-regulated Epo expression (9). Apart from Epo, we recently demonstrated hypoxic induction of several acute phase genes in HepG2 cells (10).…”
mentioning
confidence: 96%